2020
DOI: 10.1186/s12931-020-01361-9
|View full text |Cite
|
Sign up to set email alerts
|

IL-33, diet-induced obesity, and pulmonary responses to ozone

Abstract: Background: Obesity augments pulmonary responses to ozone. We have reported that IL-33 contributes to these effects of obesity in db/db mice. The purpose of this study was to determine whether IL-33 also contributes to obesity-related changes in the response to ozone in mice with diet-induced obesity. Methods: Male wildtype C57BL/6 mice and mice deficient in ST2, the IL-33 receptor, were placed on chow or high fat diets for 12 weeks from weaning. Because the microbiome has been implicated in obesity-related ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 45 publications
0
8
2
Order By: Relevance
“…Previous studies reported that IL-33 drove airway neutrophilic responses to ozone in obese mice. 26,53 In contrast, our results…”
Section: Discussioncontrasting
confidence: 94%
“…Previous studies reported that IL-33 drove airway neutrophilic responses to ozone in obese mice. 26,53 In contrast, our results…”
Section: Discussioncontrasting
confidence: 94%
“…Neutrophils are also a significant source of OSM [ 37 ]. Since we did not observe Ad vector-expressed OSM mRNA levels to be affected by IL-33 deficiency (Figures 4(c) ), the decrease in OSM protein in BALF may reflect the lack of neutrophils in the IL-33 knockout [ 35 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Carriers of 2KB upstream variant rs9990107 A and intron variant rs3836449 delCAGGGTGCCCCT (in the IL1RAP gene) are at a higher obesity risk [128]. In mice, a KO of Il1rl1 does not affect obesity levels on an HFD [198].…”
Section: Interleukins and Their Receptorsmentioning
confidence: 99%